2020
DOI: 10.1007/s10072-020-04442-1
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported needs of patients with Parkinson’s disease during COVID-19 emergency in Italy

Abstract: Because of COVID-19 outbreak, regular clinical services for Parkinson's disease (PD) patients have been suddenly suspended, causing worries, confusion and unexpected needs in such frail population. Here, we reviewed the messages spontaneously sent by patients to an Italian PD clinic during the first two weeks of COVID-19 lockdown (9-21 March 2020), in order to highlight their main needs and then outline appropriate strategies of care for this critical period. One hundred sixty-two messages were analysed. Forty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
63
1
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 5 publications
7
63
1
4
Order By: Relevance
“…Up to 80% of patients doing physiotherapy interrupted treatments during COVID‐19 emergency. Although this was felt as a major issue, 3 we did not find a significant association with health self‐perception in patients. Indeed, regardless of physiotherapy, the majority of patients, especially those with shorter disease duration, continued sport activities.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…Up to 80% of patients doing physiotherapy interrupted treatments during COVID‐19 emergency. Although this was felt as a major issue, 3 we did not find a significant association with health self‐perception in patients. Indeed, regardless of physiotherapy, the majority of patients, especially those with shorter disease duration, continued sport activities.…”
Section: Discussioncontrasting
confidence: 82%
“…Our survey was essentially focused on physical activity, however, many other factors could have contributed to patients' perception of worsening during COVID‐19 emergency. Definitely, worries about the pandemic and its consequences on health, economy, and society might have caused anxiety and stress, which is known to precipitate symptomatology in PD 3,13 . Although we roughly assessed depression by the self‐administered BDI, we could not provide a comprehensive neuropsychological evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A community-based case control study in Italy of 12 PD COVID-19 cases suggested substantial worsening of motor and non-motor symptoms during mild to moderate COVID-19 illness, independent of age and disease duration 144 , in line with an original case report series by Antonini et al In another survey across the Lombardy region of Italy, 105 probable COVID-19 cases were identified and the authors concluded that the risk, morbidity, and mortality in patients with mild-to moderate PD with COVID-19 did not differ from the general population 145 . Several viewpoints and editorials have been published on the topic in addition to extensive coverage in social media and journal viewpoint papers [146][147][148][149][150][151] .…”
Section: The Clinical Perspectivementioning
confidence: 99%
“…Whilst governments around the world are using various measures, such as lockdowns, quarantine and contact tracing, to control the spread of infection, it is worth noting that these approaches might significantly impact patients with chronic neurological disorders in unintended ways. For example, the COVID-19 quarantine in Italy created uncertainty and confusion about the availability of clinical services and continuity of care amongst PD patients [120]. Negative effects on mental health have been observed in those whose daily life was disrupted by the various public health measures [121].…”
Section: Indirect Effects Of Covid-19 On Patients With Neurological Dmentioning
confidence: 99%